A continuous, proxy-based rock mechanical approach for developing mechanical frameworks at CO2 storage sites. (June 2019) - Tenthorey, Eric; Richard, Thomas; Dewhurst, David N.
Highlights: Scratch derived unconfined compressive strength (UCS) reveals fine scale variations in rock strength within a reservoir. The scratch technique allows development of log-based proxies for strength. Application of the log-based proxy to a proximal well provides information on fault strength. Triaxial experiments provide elastic properties and strength parameters that can be compared to scratch derived results. UCS and rock stiffness appear to be correlated. Abstract: We present results from a multidisciplinary rock mechanics study designed to develop a high resolution mechanical framework of the lower Paaratte Formation, a reservoir used for CO2 storage at the CO2CRC Otway Research Facility, Otway Basin Victoria. A continuous high-resolution record of unconfined compressive strength (UCS) was determined through the scratch testing technique along approximately 80 m of CRC-2 core. Multiple correlations between UCS and several different wireline log suites resulted in the development of a strength proxy that can accurately predict strength and lithologic transitions. The strength proxy was then applied to a section of the CRC-1 well which traverses the Naylor South splay fault. The proxy predicts a UCS of approximately 20 MPa for the splay fault, which is a central learning as it constrains a key parameter that is used in fault stability modelling. A number of triaxial rock mechanical tests were also conducted to complement the scratch testing and also characterise the poroelastic properties of the various units. UCS and stiffness of the rocks appear to be positively correlated, albeit with significant data scatter and data gaps at moderate strength values. The workflow developed in this study provides a more accurate and higher resolution mechanical framework to be developed at potential CCS sites and provide a predictive methodology for mechanical properties when actual mechanical tests may be absent.